Krajowa pomoc regionalna w polityce konkurencji Unii Europejskiej - Korbutowicz, Teresa (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
Control of public aid is a component of the EU competition policy and like the policy itself is subordinated to the pursuit of integration objectives. The explicit ban on public aid from Article 1071 of the TFEU has, in fact, numerous exceptions justified by the requirements of other EU policies. National regional aid, as one of the rules of horizontal aid, is an example of such exceptions to the ban. Conditions for granting it are linked to the socio-economic cohesion policy and the implementation of the current Europe 2020 strategy. Restriction of competition by public aid is justified by a need to ensure employment, boost economic activity in the regions through aided investments and eliminate regional disparities. Allowing a possibility of public aid is always connected with a risk of distorting competitive market structures. The EU has concluded that effective control of regional aid of the member states is a prerequisite for these states’ effective regional aid policy and contributes to the achievement of the objectives of the Europe 2020 strategy.
Keywords: Unia Europejska; polityka konkurencji; krajowa pomoc regionalna; pomoc regionalna